Upaya Meningkatkan Hasil Belajar Peserta Didik Materi AlJabar Melalui Pendekatan Literasi di Kelas VII.E SMP Negeri 17 Kota Bogor - Siti Amalia (JURNAL KAJIAN ISLAM MODERN, 2021)
The low literacy culture of the Indonesian nation is caused by a lack of understanding of reading culture because generally they can only read and write. Literacy should be more comprehensive, namely the integration of listening, speaking, writing, reading and critical thinking skills. This research was conducted on mathematics subject matter Algebra in class VII SMP Negeri 17 Bogor City. The stages in this classroom action research (CAR) include (1) Planning CAR, (2) Implementing CAR, (3) Carrying out observations, and (4) Do reflection. In the first cycle obtained 34.6% results and have not reached the KKM (75). Difficulties of students in cycle I are students who are not yet skilled at differentiating similar and dissimilar tribes, so students still add or subtract different tribes. In cycle II, the learning percentage was 69.2%, and students were accustomed to writing reports and answering questions while discussing with their groups. In the third cycle, the results of learning completeness were 93.3%. Action observation data and learning outcomes in cycle III described that learning algebraic concepts was considered good based on the literacy approach. Students already have the ability to answer quiz questions with good categories. Thus, the results of this study from cycles I, II, and III showed a significant increase in learning outcomes.